Social Media Slang and Its Challenges Towards Language Literacy - Yulia Adiningsih; Yusuf Haryanto; Ana Ratnasari (Universitas Muria Kudus, 2026)
The development of social media has significantly transformed communication practices and language use, particularly through the emergence of slang language. The extensive use of slang on social media potentially influences users’ language literacy. This study aims to describe the forms of slang language used on Instagram, TikTok, and X and to analyze the challenges they pose to language literacy. This research employed a descriptive qualitative approach, with data consisting of posts, captions, comments, and tweets from public accounts collected over a period of one to two months. Data were gathered through non-participant observation and documentation, and analyzed through identification, classification, and interpretative analysis. The findings reveal that slang language on social media is predominantly manifested in the forms of word shortening, acronyms, wordplay, loanwords, and digital metaphors or idioms. The use of slang presents challenges to language literacy, particularly in terms of lexical accuracy, language structure, and contextual awareness. This study highlights that slang language should not be regarded merely as language degradation, but as a linguistic phenomenon that necessitates the reinforcement of language literacy adapted to the realities of digital communication.